Ephedrine versus phenylephrine: effects on fetal acid-base status during spinal anesthesia for elective cesarean delivery - Kumari, Pradeep; Tahir, Sifna; Mir, Altaf Ahmad; Kumari, Haveena (International Journal of Advances in Medicine, 2019)
Background: During elective caesarean sections, post-spinal hypotension is a common problem. Prevention of this complication by sympathomimetic agents is of potential clinical significance. The objective of this study was to compare and evaluate the effects of ephedrine and phenylephrine on the fetal outcome when used in the treatment of maternal hypotension during spinal block in elective caesarean section. Methods: After fulfilling the inclusion criteria, hundred patients were enrolled in this study and were randomly allocated into two groups of fifty each. According to their group, patients received either ephedrine 6 mg (group E) or phenylephrine 75µg (group P) as vasopressor. For spinal anaesthesia lumber puncture was done in sitting position and 12.5mg, 0.5% hyperbaric bupivacaine was given intra-thecally to every patient. Throughout surgery, maternal and neonatal complications were controlled and recorded. During the study, Apgar scores on the 1st and 5th minutes, and blood gases of the umbilical cord blood were evaluated. Results: Ephedrine and phenylephrine were used in the mean doses of 6.72±1.97mg and 91.5±31.38µg respectively. There was no significant difference observed in total number of boluses used in treating post-spinal hypotension. The difference in the first- and fifth-minute Apgar scores was statistically insignificant between the group E and group P. There was a statistically significant difference observed in SaO2 and base excess in arterial gas sample between two studied groups. Similarly, a significant difference was observed in PCO2 of umbilical venous sample between two studied groups. However, none of the neonates had the true fetal acidosis. Conclusions: Intravenous phenylephrine 75µg and ephedrine 6 mg offer a comparable hypotensive control without any significant complication for mother or her fetus in elective caesarean section.